2021
DOI: 10.1039/d1ja00088h
|View full text |Cite
|
Sign up to set email alerts
|

Improved determination of technologically critical elements in sediment digests by ICP-MS/MS using N2O as a reaction gas

Abstract: The investigation of technologically critical elements (TCEs) as emerging pollutants is a constantly growing field of environmental research and societal concern. Nevertheless, existing data for most TCEs are still unsatisfactory...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…5, N2O, CO2, and CH4 were also used in multiple reports instead of the default cell gases. By using N2O as the cell gas, the production rate of the oxide ions of (Mn, Fe, Ni, Cu, Zn, and Se), 1 Sr, 3,68 Br, 8 Ba, 23 (Ge, Eu, Yb) 29 and Ra, 28,45 is greatly improved in comparison to those obtained by using O2 as the cell gas. This feature provides a higher sensitivity and/or a better separation of spectral interference.…”
Section: Reaction Gases Used In the Measurement By Icp-qms/qmsmentioning
confidence: 99%
See 1 more Smart Citation
“…5, N2O, CO2, and CH4 were also used in multiple reports instead of the default cell gases. By using N2O as the cell gas, the production rate of the oxide ions of (Mn, Fe, Ni, Cu, Zn, and Se), 1 Sr, 3,68 Br, 8 Ba, 23 (Ge, Eu, Yb) 29 and Ra, 28,45 is greatly improved in comparison to those obtained by using O2 as the cell gas. This feature provides a higher sensitivity and/or a better separation of spectral interference.…”
Section: Reaction Gases Used In the Measurement By Icp-qms/qmsmentioning
confidence: 99%
“…Research fields and objectives. The research fields of the above references covered biology, 1-15 energy, 16 environment, 9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] food/medical, 10-12,25-27,33-40 geology, 28,41-47 material, [48][49][50][51][52][53][54][55][56][57][58][59][60] and radionulide, 4,[22][23][61][62][63][64][65][66][67][68][69][70][71] respectively. In addition to these conventional elemental analysis topics, a study on the gas phase catalytic reaction has also been reported by using the reaction cell of ICP-QMS/QMS as the in-situ reaction field.…”
Section: References Investigatedmentioning
confidence: 99%
“…All measurements were conducted using a tandem mass spectrometer with inductively coupled plasma (ICP-MS/MS) using an optimized method for the measurement of TCEs in sediment digests (Klein et al 2021 ). The ICP-MS/MS system consists of an Agilent 8800 ICP-MS/MS (Agilent 8800, Agilent Technologies, Tokyo, Japan) coupled to an ESI SC-4 DX FAST autosampler (Elemental Scientific, Omaha, Nebraska, USA) equipped with an ultra-low penetration air (ULPA) filtration unit (Elemental Scientific, Omaha, Nebraska, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, transboundary committees urge actions for the protection of the good environmental status, e.g., stated in the sustainable development goals (SDGs) of the United Nations or the Oslo-Paris-Convention (OSPAR). However, besides the continuously monitored legacy pollutants (e.g., Ni, Cu, Zn, Cd, Hg, Pb), new potential contaminants like the so-called technology-critical elements (TCEs) (including Ga, Ge, Nb, In, REEs and Ta) may play an important role in the near future (Filella and Rodriguez-Murillo 2017 ; Filella and Rodushkin 2018 ; Klein et al 2021 ; Nuss and Blengini 2018 ; Reese et al 2020 ).…”
mentioning
confidence: 99%
“…However, low formation of the CaO + product ion renders this approach unfavourable [ 11 ]. Nitrous oxide (N 2 O), on the other hand, is a more reactive alternative to oxygen [ 12 , 13 ] and has been explored recently for a number of elements using ICP-MS/MS systems [ 14 16 ], highlighting a broad scope for use in routine multi-element analysis. While N 2 O shows high reactivity, it is notably much less corrosive than NH 3 and may serve as a suitable alternative.…”
Section: Introductionmentioning
confidence: 99%